PENGENDALIAN RESIKO BAHAYA NAIK TURUN TANGGA DENGAN MEMASANG ANTI TOE SLIP DAN PENERAPAN THREE POINT CONTACT DI AREA SRU PERTAMINA RU IV CILACAP - Umam, Khotibul; Tirta, Andy (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
The occupational hazard risks that generally occur in the RFCC refinery area, namelythe event of a fall while going up or down stairs. Usually this happens because of the concept of threethe point of contact is often overlooked, namely the safe and secure use of the stairsmaintains three points of contact at all times. In addition, anti-coin innovation is also appliedslip as a double safety in working when going up and down stairs. The purpose ofThis study was to determine the effect of using anti toe slip and threepoint methodcontact in going up and down stairs and the level of understanding of workers in educationregarding the risk of hazards in the area of ??the RFCC Pertamina RU IV Cilacap Refinery. Toget comprehensive data in research, used qualitative analysis methodsdescriptive, where the data is translated from the results of field observations in the form of interviewsand a questionnaire with relevant questions. Furthermore, the data is analyzed and presentedin the form of a diagam or histogram. This study shows that the use of antitoe slip and the application of three point contact is very important because it canminimize the occurrence of falls when going up and down stairs during work.As many as 64% and 24% of respondents stated that the use of this method was very strongit is safe to work at a height because of the safety equipment that prevents slipperywhen going up the stairs. While the concept of thee point contact can help workers tocontinue to focus on positioning the hands and feet while on the stairs so that the incidentfalling can be avoided. Providing education about the use of anti toe slip and threepoint of contact is a factor that also determines the level of security at work atthe height when using the stairs. Of the 50 respondents who were observed, as much as 94%I totally agree that education makes workers more understanding and awarewith safety equipment that must be used and of course prevent fromrisk of falling while climbing stairs.